FORMATION OF SHOE LEATHER FROM SPLIT PIG HIDES - DANYLKOVYCH, Аnatolii; LISHCHUK, Viktor (Herald of Khmelnytskyi National University. Technical sciences, 2023)
The technology of forming patent leather has been developed from highly porous semi-finished chrome-tanned pig hides, obtained after their doubling according to the method of public JSC "Chynbar" Ukraine, Kyiv. Finishing of the tanned semi-finished product TU-U 00302391-03-98 is performed using acrylic priming compositions and polyurethanes (PU) of different chemical composition. Acrylic pigmented performer is applied to the surface of the semi-finished product after its absorption properties are equalized by double application of acrylic non-pigmented primer. The priming PU composition has a chemical composition, %, – wt.: pigment concentrate, 40% – 20.0; PU latex, 20% - 80.0; water - up to a density of 1.07. PU solutions of different chemical composition are used for both options for forming the coating on a leather semi-finished product. In particular, PU linear structure PPE-201 based on ether and PU reactive composition (RZK). The investigated film-forming reagents form highly elastic films of high strength.The use of pigmented aqueous polyurethane latex made it possible to reduce the duration of the priming stage and the consumption of the priming composition compared to the previous acrylic leveling and pigmented priming by two times, and to increase the adhesion of the coating to the semi-finished product by 18–21%. It was established that the use of polyurethane latex and the reactive polyurethane composition contributes to the formation of lacquer leather with increased resistance to wet friction by 27% and somewhat higher hygienic properties. According to the complex of physical and chemical properties, the investigated patent leathers meet the requirements of DSTU 2726-94 "Leathers for shoe uppers. Technical requirements" and industrial samples prevail and can be used for the production of model shoes.
Keywords: chrome tanning semi-finished product; split pig hide; priming; polyurethane coating; adhesion; patent leather; physical and mechanical properties